Pakistan and India’s Membership in SCO: Implications for Bilateral Cooperation - Riaz A. Khokhar (CISS Insight Journal, 2018)
This paper attempts to investigate whether the Shanghai Cooperation Organization (SCO) can play a meaningful role in defusing the tension in the bilateral relations of India and Pakistan. The purpose of this study is to explore if SCO has a role in bringing both India and Pakistan closer. With the help of both primary and secondary sources, this study looks at India Pakistan relations through the paradigm of liberalism. Although liberalism sees resolution of bilateral territorial disputes in economic interdependence, this research has concluded that Pakistan considers resolution of outstanding disputes, especially Kashmir, as a precursor to the bilateral trade. Hence, the role of regional institutions such as Shanghai Cooperation Organization (SCO) will remain contingent upon these factors.